Pulmonary Edema in Healthy Subjects in Extreme Conditions - Garbella, Erika; Catapano, Giosuè; Pratali, Lorenza; Pingitore, Alessandro (Pulmonary Medicine, 2011)
There are several pieces of evidence showing occurrence of pulmonary edema (PE) in healthy subjects in extreme conditions consisting of extreme psychophysical demand in normal environment and psychophysical performances in extreme environment. A combination of different mechanisms, such as mechanical, hemodynamic, biochemical, and hypoxemic ones, may underlie PE leading to an increase in lung vascular hydrostatic pressure and lung vascular permeability and/or a downregulation of the alveolar fluid reabsorption pathways. PE can be functionally detected by closing volume measurement and lung diffusing capacity test to different gases or directly visualized by multiple imaging techniques. Among them chest ultrasonography can detect and quantify the extravascular lung water, creating “comet-tail” ultrasound artefacts (ULCs) from water-thickened pulmonary interlobular septa. In this paper the physiopathological mechanisms of PE, the functional and imaging techniques applied to detect and quantify the phenomenon, and three models of extreme conditions, that is, ironman athletes, climbers and breath-hold divers, are described.